Competencias genéricas del proyecto Tuning para América Latina (2015)
This paper aims to discuss some of the general powers of the Tuning Project for Latin America, identifying the importance of such an analytical and illustrative aim for a more detailed description thereof. To fulfill this objective a documentary investigation arises, with a descriptive analysis, used as the basis further information on the purpose of each treated competition.